Analysis of the Effect of Non-Cash Payments on the Velocity of Money in Indonesia - Valencia, Selen Chaterine; Sishadiyati, Sishadiyati (PT. Riset Press International, 2024)
The purpose of this study is to analyze how the effect of non-cash payments on the Velocity of Money. This study used a quantitative approach and used multiple linear regression as the data analysis method. The population in this study is the territory of Indonesia, the sampling technique uses non-probability sampling with a type of saturated sampling technique. The secondary data used is a time series within a period of 14 years, the period 2009 to 2022 in annual form. The results of this study show that from the results of t Test, ATM/Debit Cards have a significant negative effect on the Velocity of Money. Credit Cards have a significant positive effect on the Velocity of Money. However, E-Money does not affect the Velocity of Money. Meanwhile, based on the F Test result, ATM/Debit Cards, Credit Cards, and E-Money simultaneously have a significant effect on the Velocity of Money at a confidence level of 93%. This research provides benefits for the government, society, and other institutions in the form of steps and attitudes that need to be taken to increase non-cash payment transaction value to increase the Velocity of Money in Indonesia.